PENGGUNAAN BEBAN PENDORONG UMPAN YANG TEPAT PADA HASIL PERAJANGAN KERIPIK SINGKONG - Sukadi Sukadi (TEKNIKA: Jurnal Teknik, 2016)
The driving load of cassava feed in the cutting process has an influence on the result of cuts cassava chips. This study aims to get a load of cassava feed right that the thickness of cassava cutting results obtained homogeneous and maximum capacity. This study to use the machine design result dimensions of 600 mm x 455mm x 505 mm, blade shaft speed 310 rpm at the Maintenance and Repair Laboratory of Polytechnic Jambi. The data taken is the thickness and when the results of cutting using a plunger load of bait 300 g, 600 g and 900 g. From the research results obtained thickness cuts for all homogeneous load is 1 mm, while for the cutting time with a load of 300 g, 600 g and 900 g respectively take 10.53 seconds, 8.63 seconds and 8.05 seconds. It is concluded that cutting the right time to get the homogeneous and the shortest time possible using the driving load of 900g. Keywords: cutting, driving load, homogeneous